Mugilidae fish as bioindicator for monitoring plastic pollution: Comparison between a commercial port and a fishpond (north-western Mediterranean Sea). (April 2022) - Reboa, Anna; Cutroneo, Laura; Consani, Sirio; Geneselli, Irene; Petrillo, Mario; Besio, Giovanni; Capello, Marco
Abstract: In the last decade, interest in monitoring and managing plastic pollution has greatly increased. This study compared levels of microplastic contamination in stomachs of Mugilidae fish, suggesting this family as a target for plastic pollution monitoring in areas with different degrees of anthropisation. Two sites characterised by low and high anthropic impact, a fishpond (S'Ena Arrubia, Italy) and a port (Genoa, Italy), respectively, were compared. This study highlighted a stronger microplastic contamination in the port, with a higher percentage of fish showing the presence of microplastics and a larger polymeric variability compared to the fishpond. The microplastic number in fish from the port was higher than in the literature, but it was not significantly different from S'Ena Arrubia in terms of the microplastic percentage found in single individuals. Biomonitoring of microplastic contamination in Mugilidae fish resulted in a valid tool for the investigation of areas differently affected by human activity. Graphical abstract: Unlabelled Image Highlights: Deepening of plastic pollution investigation in highly anthropized areas as ports Comparison between areas differently affected by human activities Mugilidae fish as a tool for microplastic pollution biomonitoring